The Power of Gamification in Online Sessions - Espíritu, Julio; Espíritu, Elizabeth (CIEX JOURNAL, 2025)
Gamification and game-based teaching play an acute role in learning outcomes and classroom climate. Gamifying the language classroom sharply improves the learning environments. Learning outcomes and a welcoming classroom climate are vivified by our teaching techniques. Thus, it is important to learn new information, and new currents and study them, especially in this era defined by rapid technological advancements and evolving educational paradigms. Our educational and teaching practices should evolve together with the traditional struggle to fully captivate our students and create an assured learning experience and environment. Hence, the importance of learning about this mostly unexplored teaching technique.